The influence of parental attention on student learning achievement in elementary school - Erpan Susanto; Darma Putra; Sayida Khoiratun Nisak (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2024)
One of the roles of parents in the success of their children's education is to pay attention, especially attention to learning activities. The method used is quantitative research. quantitative research is research that is required to use a lot of numbers, starting from data collection, interpretation of the data, and the appearance of the results. This research design uses quantitative research with survey research methods. This research was conducted in February-July 2021. This research was conducted at SDN 097 / IV Jambi City, INHIL Riau Regency with 154 students consisting of 84 boys and 70 girls. Based on the results of the study, it was found that there was a significant effect of parental attention on the learning achievement of students in grades IV and V of SDN 097 / IV Jambi City. This result is evident from the value of tcount> ttabel 5.885> 2.021 (significant level 0.05) and also evident from the value of tcount> ttabel 5.885> 2.704 (significant level 0.01). The regression results also show a positive regression coefficient value, which means that there is a significant positive effect of parental attention on student learning achievement, which means that the better the attention of students' parents, the better their learning achievement will be. The percentage contribution of the influence of parental attention variables on student learning achievement is 42.96% while the rest is influenced by other factors. The results of the analysis that have been carried out also show that the correlation coefficient of the influence of parental attention on student learning achievement is 0.655. This value shows that the effect of parental attention on student learning achievement is classified in the strong category, because the correlation coefficient value is in the interval 0.5999 - 0.7999 with a correlation level classified as